Cecil Polhill: Missionary, Gentleman and Revivalist : Volume1 (1860-1914) - Usher, John, (Global Pentecostal and Charismatic Studies ;, 2020)
The full significance of Cecil Henry Polhill (1860-1938), the wealthy squire of Howbury Hall, is known to few, yet he was one of the founding fathers of the Pentecostal-Charismatic tradition in Britain, and his impact and legacy stretch far beyond British shores to North America, the Far East and elsewhere. In Cecil Polhill: Missionary, Gentleman and Revivalist John Usher comprehensively connects Polhill's early life and former experiences as an Evangelical Anglican missionary in China, a member of the Cambridge Seven, with his time as a pioneer of early Pentecostalism, and in doing so reveals a much more richly contoured and multifaceted picture of the development of early Pentecostalism than previously achieved.